- Thread starter
- #1

E(Xg(Y)) = E(E(X|Y)g(Y))

for any function g. Using this definition show that E(aX|Y ) = aE(X|Y ).

so according to the definition do i start with this?:

E(aX|Y) = E(aE(X|Y)|Y)

if so how do i continue from there?

- Thread starter oyth94
- Start date

- Thread starter
- #1

E(Xg(Y)) = E(E(X|Y)g(Y))

for any function g. Using this definition show that E(aX|Y ) = aE(X|Y ).

so according to the definition do i start with this?:

E(aX|Y) = E(aE(X|Y)|Y)

if so how do i continue from there?